Effectiveness of physical activity interventions on reducing perceived fatigue among adults with chronic conditions: a systematic review and meta-analysis of randomised controlled trials - Ioulia Barakou; Kandianos Emmanouil Sakalidis; Ulric Sena Abonie; Tracy Finch; Katie L. Hackett; Florentina Johanna Hettinga (Scientific Reports)
Abstract Fatigue is barrier of physical activity participation in adults with chronic conditions. However, physical activity alleviates fatigue symptoms. This systematic review and meta-analysis aimed to (1) synthesise evidence from randomised controlled trials (RCTs) exploring the effects of physical activity interventions on fatigue reduction and (2) evaluate their effectiveness. Medline/CINAHL/EMBASE/Web of Science and Scopus were searched up to June 24th, 2023. Two reviewers independently conducted study screening and selection (RCTs), extracted data and assessed risk of bias (RoB2). Outcome was the standardised mean difference (SMD) with 95% confidence intervals in fatigue between experimental and control groups. 38 articles met the inclusion criteria. Overall, physical activity interventions moderately reduced fatigue (SMD = 0.70 p < 0.0001). Interventions lasting 2–6 weeks and 16–24 weeks demonstrated the larger effects on fatigue reductions (SMD=0.86, p<0.00001; SMD=1.82, p=0.01, respectively). Interventions with 30-36 sessions showed a large effect on fatigue reduction (SMD = 0.94, p < 0.04). Resistance, aerobic cycling and combination training interventions had a large to moderate effect (SMD= 0.93, p 0.03; SMD = 0.66, p= 0.0005; SMD = 0.76, p = <0.00001, respectively). Small long-term effects were found during follow-up(SMD=0.38, p= 0.002). Notably, both short (2-6 weeks) and longer-term (16-24 weeks) interventions were effective in reducing fatigue. . Physical activity interventions moderately reduced fatigue among adults with chronic conditions. Duration, total sessions, and mode of physical activity were identified as key factors in intervention effectiveness. Further research is needed to explore the impact of physical activity interventions on fatigue.